Management scheme for autonomic load balancing of TD-SCDMA wireless access network - ZHANG Heng1; QIU Xue-song1; MENG Luo-ming1; GAO Zhi-peng1; ZHANG Xi-dong3 (Tongxin xuebao)
A new autonomic load balancing management scheme-game theoretic diffluence autonomic load balance scheme（GDALB） was proposed based on autonomic management techniques and game theory.It is proved that the key algorithms are convergent and the optimum local solution can be gained.Simulation results show that,comparing with existing schemes,GDALB causes larger system capacity,and can address problems such as uncontrollable overlap area;held back of balance action caused by handover scheme.